Stability criteria for volterra type linear nabla fractional difference equations - Gevgeşoğlu, Murat; Bolat, Yaşar (Springer Science and Business Media LLC, 2022)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Stability theory for difference equations; Difference equations, scaling (\(q\)-differences); nabla fractional difference equations; Volterra difference equations; stability